Thermodynamic consistency in deriving lattice Boltzmann models for describing segregation in non-ideal mixtures - Philippi P.C. (2011)
The thermodynamic consistency of kinetic models for non-ideal mixtures in nonisothermal conditions is investigated. A kinetic model is proposed that is suitable for derivinghigh-order lattice Boltzmann equations by an appropriate discretization of the velocity space, satisfying the Galilean invariance condition and free of spurious terms in the first moment equations. © 2011 The Royal Society.